THE SADF AND CONSERVATION - Bisset, E.M.; Bisset, W.M.; Murray, Kevin (Scientia Militaria - South African Journal of Military Studies, 2012)
Admiralty House is the oldest and unquestionably the most interesting building in Simonstown. It was originally the home of Antoni Visser, a former Dutch soldier whose willingness to serve as the Dutch East India Company’s unofficial representative in Simon’s Bay probably encouraged him to build the house. A double-storeyed house approximately on the site of the present Admiralty House is shown on a map dated circa 1740.